Kreativitas Guru dalam memanfaatkan berita politik sebagai media pembelajaran kelas IX di SMP Negeri 31 Padang - Rina Fitri (Journal of Civic Education, 2018)
The goal of this study is 1) describe the creativity of teachers in using online political news as a medium of learning on civic education subject at Class IX in SMP Negeri 31 Padang. 2) identify the obstacles of teachers in using online political news as a medium of learning on civic education at Class IX in SMP Negeri 31 Padang. This research uses qualitative approach with descriptive method. The result of the research shows that the first form of teacher's creativity in using online politics news as a learning media of civic education can be seen through five stages: planning stage, preparatory phase of teacher, class preparation stage, learning implementation using political news media, and evaluation stage. Both teachers' obstacles in using the political news media are caused by several factors including teachers still difficulty in formulating learning indicators, less supportive school facilities, poor internet access, too short learning time allocation, and some students are less fond of political news. The benefits of the news media politics on civic education subject can increase students' political knowledge, students can distinguish the political problems with other problems, and can know the current political problems. In addition, learning by using the political news media to make students more active in learning, students are more motivated to follow the learning of civic education subject.